Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1999
DOI: 10.1115/99-gt-390
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Achieving Accurate Numerical Simulation of Tip Clearance Flows in Transonic Compressor Rotors

Abstract: The tip clearance flows of transonic compressor rotors are important because they have a significant impact on rotor and stage performance. While numerical simulations of these flows are quite sophisticated, they are seldom verified through rigorous comparisons of numerical and measured data because these kinds of measurements are rare in the detail necessary to be useful in high-speed machines. In this paper we compare measured tip-clearance flow details (e.g. trajectory and radial extent) with corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 12 publications
3
33
1
Order By: Relevance
“…hub clearance of 1.62% hub chord), and mixed flow rotor (max. tip clearance of 1.28% tip chord) were, respectively, 24, 38, and 96, all of which surpass the criterion proposed by Van Zante et al [4] for adequate capture of tip clearance flow. + value at the solid surfaces goes from below 1 up to 6.…”
Section: Computational Setupmentioning
confidence: 46%
See 1 more Smart Citation
“…hub clearance of 1.62% hub chord), and mixed flow rotor (max. tip clearance of 1.28% tip chord) were, respectively, 24, 38, and 96, all of which surpass the criterion proposed by Van Zante et al [4] for adequate capture of tip clearance flow. + value at the solid surfaces goes from below 1 up to 6.…”
Section: Computational Setupmentioning
confidence: 46%
“…On the other hand, one may choose to use an existing in-house compressor rig to perform new specific tests for code assessment. Van Zante et al [4] performed tip clearance flow LDV measurements on an existing NASA Rotor 35 to assess the accuracy of numerical tip clearance flow predictions. To validate numerical simulations of more complex compressors, Mansour et al [5] and Cornelius et al [6] validated their computational solutions with measurements obtained from their multistage transonic compressor rig.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, in addition to the analysis of geometric parameters, the selection of parameters of the calculation model, such as: the computational domain, grid parameters, boundary conditions, solver settings, etc., is of great importance in solving the optimization problem [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, computational fluid dynamic (CFD) techniques have been also introduced as a powerful tool to characterize the impact of tip leakage structures onto the passage-averaged flow. Some strategies assume that there is flow periodicity across a non-gridded region above the blade tip, whereas others consists in fully gridding the gap with a separate grid block [15,16]. In case of gridding the gap, the model requires intensive computational resources due to the near-wall grid spacing recommended for the tip gap.…”
Section: Introductionmentioning
confidence: 99%
“…In case of gridding the gap, the model requires intensive computational resources due to the near-wall grid spacing recommended for the tip gap. It has been demonstrated that such a grid distribution has a significant impact on accurate prediction of the clearance flow [16].…”
Section: Introductionmentioning
confidence: 99%